Semias fílmicas en una novela policiaco-existencial de Mario Lacruz: El inocente (1953) (El Hilo de la Fabula, 2021)
The history of the relationship between cinema and literature has been constant, and has had as its main topic of interest the study of film adaptations of literary works in the field of comparatism. However, other types of interferences that occur between both media, such as the influence of film codes on literature have been neglected. From this perspective, the purpose of this paper is to demonstrate how Mario Lacruz, in his novel El inocente (1953), uses film semias to construct the narrative point of view, time and space.
Keywords: Comparative literature; Cinema and literature; Film semias; Mario Lacruz; El inocente